Союз Пілсудського – Петлюри в історії боротьби за українську державність - Верстюк, В. (Український історичний журнал, 2020)
Аналізується перебіг українсько-польських відносин часів Української революції 1917–1921 рр., перехід від фази збройного протистояння до налагодження союзницької взаємодії, спрямованої на відсіч спільному ворогові – російському більшовизму. Методика дослідження спирається на загальні наукові методи аналізу, історизму, порівняння, деталізації та узагальнення. Також застосовано компаративний і структурний методи. Події 1919–1920 рр. розглядаються у широкому міжнародному контексті становлення Версальської політичної системи, геополітичного переформатування Центрально-Східної Європи. Наукова новизна. На основі української та польської історіографії, через уведення до наукового обігу низки нових архівних матеріалів фокусується увага на процесі становлення українсько-польських дипломатичних відносин, дипломатичній місії на чолі з А.Лівицьким, її прибутті до Варшави у жовтні 1919 р., дискусіях із польськими політиками з приводу визначення майбутнього міждержавного кордону. Чинниками, що справляли вагомий вплив на переговорний процес, стали поразки військ УНР, перехід Української галицької армії на бік ґенерала А.Денікіна, жорсткі вимоги Варшави щодо включення до складу II Речіпосполитої Східної Галичини й Західної Волині, вимушене визнання українською стороною територіальних втрат, їх фіксація в декларації від 2 грудня 1919 р., реакція вітчизняних політиків на поступки уряду УНР, роль Ю.Пілсудського й С.Петлюри в підготовці договору, завершення переговорного процесу, підписання політичної та військової конвенцій і похід об’єднаних сил на Київ. Детально розкривається непростий, сповнений компромісів процес пошуку шляхів до порозуміння, що зрештою призвело до єдності у протистоянні спільному ворогові. У висновках констатується, що Варшавський договір залишається дискусійною подією. Оцінки його позбавлені однозначності та спрощеного неґативізму. Наголошується, що хоч тодішній союз і був нерівнозначним, проте дозволив продовжити боротьбу за українську незалежність до кінця 1921 р., а сьогодні є історичним плацдармом для формування позитивної візії українсько-польських стосунків. The article is dedicated to the anniversary of the Treaty of Warsaw. The author aims to analyze the course of drawing up Ukrainian-Polish relations during the Ukrainian Revolution of 1917–1921, transition from military confrontation to union restoration in order to repel the common enemy – Russian Bolshevism. The research methodology is based on common scientific methods of analysis, historicism, comparison, detailing and generalization. Comparative and structural methods have also been applied. Events of 1919–1920 are considered in the wide international context of the formation of the new Versailles political system, geopolitical reformation of Central and Eastern Europe. Scientific novelty. Using Ukrainian and Polish historiography, introducing a number of new archival materials into the scientific circulation, the author focuses his attention on the process of formation of Ukrainian-Polish diplomatic relations, establishing a Ukrainian diplomatic mission led by A.Livytskyi, arriving of the Ukrainian diplomatic mission in Warsaw in October 1919, setting up a negotiation process, discussions with Polish diplomats on defining the future Ukrainian-Polish border. Collapse of the UPR Army, transition of the Ukrainian Halychyna Army to the side of general A.Denikin as a factor in the weakening of Ukrainian positions. Strong demands of the Poles to include Eastern Halychyna and Western Volyn in Polish-Lithuanian Commonwealth. Forced recognition of the territorial losses by the Ukrainian side, stated in the mission declaration as of December 2, 1919. Reaction of the Ukrainian elite to the territorial concessions of UPR government. Role of J.Piłsudski and S.Petliura in the preparation of the treaty, completion of the negotiation process, signing the political and military conventions. Military campaign of the union armies to Kyiv. The article details the dramatic process of finding a path to mutual understanding, a path filled with compromises that ultimately led to unity in the fight against a common enemy. The findings state that this event was, and still is, scientifically relevant and debatable among historians. However, the estimates of the Treaty of Warsaw are devoid of ambiguity and simplistic negativism, they emphasize that the union, although not equivocal, allowed to continue the struggle for Ukrainian independence till the end of 1921, and today it is a historic springboard for the formation of a positive vision of the Ukrainian-Polish relations.